On the demonstration of the normal polarity of remanent magnetization by volcanic rocks containing magnetite or hematite - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2010)
Magnetic and paleomagnetic properties, and magnetic mineralogy of theNeogene andesitic rocks were previously studied. The author of the article has recentlyproposed a model of the sources of normal and reversed RM and tested it applying theresults of the submarine volcanics (Orlický, 2010). The magnetites (cubic phase) andthe titanium rich titanomagnetites (cubic phase) have been considered as the carriers ofonly normal remanent magnetization of the rocks. The low-temperature oxidized titanomagnetitesand the Ilmenite-Hematites (Ilm-Hem; rhombohedral phase) carry either thereversed remanent magnetism (RM) of self-reversed origin, or normal RM, depending onthe proportion of hematite in the Ilm-Hem solid solutions. I have enlarged the originalmodel in the hematite bearing rocks which carry only normal RM. The paleomagneticand magnetic results and the results of magnetic mineralogy of selected Neogene andesitesand rhyolites from central, southern and eastern Slovakia of the Badenian to the Middleor Lower Sarmatian age (16.05–12.9 M.Y.) have been considered. The selected rockswith the magnetites and hematites have revealed only the normal RM. Normal partialthermoremanent magnetization (PTRM) was induced in many magnetites and hematitescontaining andesite and rhyolite samples in the laboratory. The occurrence of both thesetypes of magnetic minerals is quite rare in volcanics. While the magnetite is more frequentlypresent in the intrusive rocks, the hematite is frequently present in effusive, moreacidic volcanics, e.g. in the rhyolites. Very important outcome is that both magnetiteand hematite are the carriers of only normal polarity of RM in the rocks, regardless theirage.